2016
DOI: 10.1007/s00520-016-3316-x
|View full text |Cite
|
Sign up to set email alerts
|

Opioids for management of episodic breathlessness or dyspnea in patients with advanced disease

Abstract: Although the pathophysiology and mechanism of action of opioids for management of breathlessness, and specifically EB, are not fully known, there is scientific evidence, and particularly great clinical evidence, of the benefit of this drug class for dyspnea management. It is important to differentiate hospitalized patients from outpatients because venous or subcutaneous access is easier in hospitalized patients, but use of transmucosal fentanyl, especially in faster formulations like intranasal application, op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Our findings are consistent with other reviews on opioids for chronic breathlessness [5, 6, 86] and episodic breathlessness [87]. These reviews included RCTs [5,6,86,87], NRTs [6,86] and case reports [87].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with other reviews on opioids for chronic breathlessness [5, 6, 86] and episodic breathlessness [87]. These reviews included RCTs [5,6,86,87], NRTs [6,86] and case reports [87].…”
Section: Discussionsupporting
confidence: 92%
“…Dosage regimens, as presented in the opinion from the CONTAM Panel from 2011, are confirmed in recent reviews and monographs (e.g. Currow et al., ; Kohberg et al., ; Cabezon‐Gutierrez et al., ; Martindale, ). However, in newer literature, further research needs are suggested to investigate upwards titration of dosages under aspects of therapeutical benefits and reduction of adverse effects (Currow et al., ; Verberkt et al., ).…”
Section: Assessmentmentioning
confidence: 67%
“…8,[14][15][16][17] For example, oxycodone and fentanyl are potential substitutes for morphine in the palliative treatment of dyspnea. [9][10][11][18][19][20][21][22][23] There are a variety of efficacious ways to administer opioids for breathlessness relief. Oral and parenteral opioid formulations are particularly successful in minimizing dyspnea.…”
Section: Subheading Of "Pharmacologic Management: Opioids": Morphine ...mentioning
confidence: 99%